2022
DOI: 10.1093/neuonc/noac123
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of children ≤36 months of age with DIPG: A report from the international DIPG registry

Abstract: Background Children ≤36 months with Diffuse Intrinsic Pontine Glioma (DIPG) have increased long-term survival (LTS, overall survival (OS) ≥24 months). Understanding distinguishing characteristics in this population is critical to improving outcomes. Methods Patients ≤36 months at diagnosis enrolled on the International DIPG Registry (IDIPGR) with central imaging confirmation were included. Presentation, clinical course, imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…DIPGs classically present with a rapid onset of neurological symptoms, with a median age at diagnosis of 6-7 years. 2,5,8-10,13 Our patient's progressive symptomatology over one year 4,8,12 and her relatively old age at the time of diagnosis were indicative of her potential for long-term survival. 2,4,6 Other known clinical factors that favor LTS include the lack of cranial nerve palsies at the time of diagnosis 4,9,12,13 ; however, this was not the case for our patient.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…DIPGs classically present with a rapid onset of neurological symptoms, with a median age at diagnosis of 6-7 years. 2,5,8-10,13 Our patient's progressive symptomatology over one year 4,8,12 and her relatively old age at the time of diagnosis were indicative of her potential for long-term survival. 2,4,6 Other known clinical factors that favor LTS include the lack of cranial nerve palsies at the time of diagnosis 4,9,12,13 ; however, this was not the case for our patient.…”
Section: Discussionmentioning
confidence: 84%
“…Bartlett et al did not find any MRI findings (tumor dimensions and extension, margins, presence of hemorrhage, diffusion restriction, enhancement morphology, degree of necrosis and hydrocephalus) predictive of survivorship, except for an absence of spinal metastases. 12 However, other authors determined that ring enhancements, 8,9,12,13 significant necrosis, 4,6,9 extrapontine extension 4 , and greater craniocaudal dimensions (other planes were insignificant 6 ) are unfavorable prognostic factors. 9 Research on MRI variables as dynamic biomarkers for progression-free survival is ongoing in DIPG, [14][15][16] although the direct role of routine follow-up imagery on survival remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An earlier study with 316 pediatric patients showed that age ≤3 years positively predicted the prognosis of DIPG. 43 Moreover, an international cohort demonstrated that DIPG patients aged ≤36 months had increased long-term survival, 44 and suggested that patients of different ages could have different prognoses, especially within the pediatric group. A recent study profiled the landscape of cell states and tumor microenvironment, which were found to be different in H3K27M-mutant DMG between the pediatric and adult patients, 45 probably accounting for the different prognoses.…”
Section: Discussionmentioning
confidence: 99%
“…On the opposite side of the epidemiological spectrum of age, it has been reported that very young children with DMG (less than three years old) might have a significantly longer OS than older patients ( 42 , 67 ).…”
Section: A Complex Biological and Clinical Picture Behind A Unifying ...mentioning
confidence: 99%